The Role of The Village Owned Business Entity ( Bumdes ) Developing Misme In Boncah Nahang Village - Samaun Yudha (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2019)
The purpose of this study is to find out how the role and obstacles for BUMDES Bina Usaha Mandiri in developing MSMEs in Boncah Mahang Village. This research was conducted because MSMEs in Boncah Mahang Village, which are starting to run, still require special attention so that in the future MSMEs in Boncah Mahang Village can be recognized and compete in a wider market.                      This type of research is a qualitative research method with a case study approach. The data collection technique used is the method of interview, observation and documentation. The data analysis technique used to answer the problems raised in the study is qualitative analysis.The results showed that the role of BUMDES in developing independent businesses in developing MSMEs in Boncah Mahang village was not maximized because BUMDES still faced several obstacles such as the lack of practitioners who understood and paid attention to MSMEs, MSMEs had not become a priority program for the village government, lack of competent human resources in the village. field and need additional operational capital. The role of BUMDES in developing independent businesses in developing MSMEs in Boncah Mahang village has a positive impact on the community's economy, especially for MSME actors.